LITERASI BUDAYA ETNIK MELALUI PEMBELAJARAN BAHASA INDONESIA DI IAIN PONTIANAK - Yusriadi Yusriadi; Dedy Ari Asfar (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2023)
This research aims to describe the efforts to improve students ' understanding and literacy in matters of ethnic culture through learning activities in Indonesian language courses in universities. This study was carried out qualitatively by using first semester students who took the subject of Indonesian in FUAD class. In this class, students are asked to keep a diary. After that, each of them was asked to provide feedback about the progress obtained after participating in the diary writing program. Data were collected through in-question and FGD as well as written questions. The Data is then processed qualitatively based on thematic approach. In conclusion, students who take Indonesian courses admit that they have made significant progress in understanding ethnic groups and cultures. Through the task of making up about different ethnic friends, the experience of participating in cross-ethnic cultural activities, they re-create positive memories about other ethnic groups. This study shows that understanding of ethnicity can be integrated through learning activities.